Management of perinatal depression by non-health specialist workers in Indonesia - Indah Rosmawatia; Mahua Das (Journal of Health Technology Assessment in Midwifery, 2018)
Perinatal depression has become a public health concern because of the burden of the disease for mother and children as well as the community in large. The management of perinatal depression is needed, yet there is a low-resource of mental health specialist in Indonesia. Psychotherapy interventions by non-health specialist workers in some developing countries have shown benefits for perinatal depression. The study aims to analyze the interventions for perinatal depression by non-health specialist workers based on studies from other developing countries. The type of the study is an in-depth study using secondary data. Data were obtained from online databases, including PubMed, Global Health Cochrane Library, PsycINFO and additional search. The total number of studies found was 743, 705 studies were available for assessment after removing the duplicate, 55 abstracts were reviewed, and 42 studies included. A conceptual framework developed by the author was used to guide data collection and analysis. Psychotherapy interventions implemented in Pakistan, Turkey, China, and India were analyzed using Assessment of Applicability and Transferability criteria. The most applicable and transferable interventions for the management of perinatal depression in Indonesia were Cognitive Behavioural Therapy and participatory women group. This study indicates that interventions by non-health specialist workers could reduce the interventions gap for perinatal depression. The stakeholders are recommended to adapt the interventions into a cultural context and integrate it into existing maternal and child health program.